Edukasi Pertolongan Pertama pada Balita dengan ISPA di Puskesmas Maccini Sawah - Sanghati Sanghati; Yantimala Mahmud; Nurbaiti Nurbaiti; Novitaradayanti Novitaradayanti; Nur Annisa Utami Putri (Universitas Muhammadiyah Manado, 2022)
Acute Respiratory Infection Disease (ARI) is an infectious disease that is still a health problem for children under five in Indonesia and is the highest cause of death rates for children under five. Apart from causing health problems, ARI can also cause death. This activity aims to increase the understanding of cadres and mothers of toddlers about first aid that can be given to ISPA toddlers. The target of this activity is 35 people. The activity method was carried out on May 16 2022 by giving a pre-test, lecture and followed by a post-test by filling out a questionnaire. The evaluation was carried out on cadres, mothers of toddlers by conducting a post test. The results achieved in this activity were that participants gained knowledge about first aid that participants should provide if their toddler suddenly becomes ill, by lying on their lap with the baby's face facing down. Do not restrain the child's body. Tilt the child's body position so that vomit or saliva can come out of the oral cavity, and prevent the tongue from blocking the respiratory tract. Loosen the child's clothing and do not put anything in the child's mouth to prevent tongue biting. Calculate the duration of the febrile seizure and pay attention to the child's behavior during the seizure. Tell this when you consult a doctor.